Konseling Individual dalam Mengatasi Peserta Didik yang Mengalami Homesick di MAN Insan Cendekia Tanah Laut - Humairah Dalila; Haris Fadillah (Sekolah Tinggi Agama Islam Al Washiliyah Barabai, 2024)
This research aims to determine the implementation of individual counseling in dealing with students who experience homesickness at MAN Insan Cendekia Tanah Laut. This research uses a type of field research. with a qualitative descriptive approach. Data collection techniques were carried out through interviews with students and guidance and counseling teachers, observation and documentation as supporting facilitation. The data analysis technique used is engineering qualitative descriptive analysis. As well as validating the data using triangulation techniques data to strengthen the validity of the data. From the research results, it was found that in an effort to overcome the problem of homesickness, the guidance and counseling teachers provided assistance through individual counseling. Individual counseling is provided through 4 activity stages, namely planning, activities planning starting from identifying students to creating RPL includes appointment time and place of meeting. Implementation is divided into three stages starting from building good relationships, exploring problems, and arriving at ensure students make changes in a positive direction. Evaluation, with a decrease in anxiety in students and follow-up activities, carry out follow-up activities on student development in collaboration with dormitory supervisors, homeroom teachers, foster teachers, and parents using techniques SFBT (Solution Focus Brief Therapy) approach, namely, focusing on solving problems being experienced by students.